Exaggerated exercise pressor reflex in male UC Davis type 2 diabetic rats is due to the pathophysiology of the disease and not aging - Huo, Yu; Grotle, Ann-Katrin; McCuller, Richard K.; Samora, Milena; Stanhope, Kimber L.; Havel, Peter J.; Harrison, Michelle L.; Stone, Audrey J. (Frontiers in Physiology, 2023)
Studies in humans and animals have found that type 2 diabetes mellitus (T2DM) exaggerates the blood pressure (BP) response to exercise, which increases the risk of adverse cardiovascular events such as heart attack and stroke. T2DM is a chronic disease that, without appropriate management, progresses in severity as individuals grow older. Thus, it is possible that aging may also exaggerate the BP response to exercise. Therefore, the purpose of the current study was to determine the effect of the pathophysiology of T2DM on the exercise pressor reflex independent of aging. We compared changes in peak pressor (mean arterial pressure; ΔMAP), BP index (ΔBPi), heart rate (ΔHR), and HR index (ΔHRi) responses to static contraction, intermittent contraction, and tendon stretch in UCD-T2DM rats to those of healthy, age-matched Sprague Dawley rats at three different stages of the disease. We found that the ΔMAP, ΔBPi, ΔHR, and ΔHRi responses to static contraction were significantly higher in T2DM rats (ΔMAP: 29 ± 4 mmHg; ΔBPi: 588 ± 51 mmHg•s; ΔHR: 22 ± 5 bpm; ΔHRi: 478 ± 45 bpm•s) compared to controls (ΔMAP: 10 ± 1 mmHg, p < 0.0001; ΔBPi: 121 ± 19 mmHg•s, p < 0.0001; ΔHR: 5 ± 2 bpm, p = 0.01; ΔHRi: 92 ± 19 bpm•s, p < 0.0001) shortly after diabetes onset. Likewise, the ΔMAP, ΔBPi, and ΔHRi to tendon stretch were significantly higher in T2DM rats (ΔMAP: 33 ± 7 mmHg; ΔBPi: 697 ± 70 mmHg•s; ΔHRi: 496 ± 51 bpm•s) compared to controls (ΔMAP: 12 ± 5 mmHg, p = 0.002; ΔBPi: 186 ± 30 mmHg•s, p < 0.0001; ΔHRi: 144 ± 33 bpm•s, p < 0.0001) shortly after diabetes onset. The ΔBPi and ΔHRi, but not ΔMAP, to intermittent contraction was significantly higher in T2DM rats (ΔBPi: 543 ± 42 mmHg•s; ΔHRi: 453 ± 53 bpm•s) compared to controls (ΔBPi: 140 ± 16 mmHg•s, p < 0.0001; ΔHRi: 108 ± 22 bpm•s, p = 0.0002) shortly after diabetes onset. Our findings suggest that the exaggerated exercise pressor reflex and mechanoreflex seen in T2DM are due to the pathophysiology of the disease and not aging.